Implementation of the Management of Anticoagulation in the Periprocedural Period App into an Electronic Health Record: A Cost-Effectiveness Analysis - Wang, Jason J.; Koulas, Ioannis; Myrka, Anne; Spyropoulos, Alex C. (Clinical and applied thrombosis/hemostasis, 2023)
The Management of Anticoagulation in the Periprocedural Period (MAPPP) app is a free tool providing up-to-date guidelines on the periprocedural management of patients on long-term anticoagulants. After validating its effectiveness in the post-procedural period, we aimed to study its overall cost-effectiveness. SF-12 surveys were sent to eligible patients, converted into SF-6D forms, and subsequently into quality-adjusted life years (QALYs) to calculate the incremental cost-effectiveness ratio (ICER). The number of 30-day readmissions was used to calculate hospitalization costs, utilizing publicly available data. From 1/1/2018 to 1/31/2019, 642 patients were screened for enrollment, with an overall response rate of 94% (164/175) among the consented and 49% (164/336) among all eligible patients. The average QALY score was 0.7134 (95% CI [0.6836, 0.7431]) for the patients whose treatment plan followed the MAPPP app recommendations (acceptance group) and 0.7104 (95% CI [0.6760, 0.7448]) for those who did not (rejection group), without statistically significant differences. The difference in ICER scores was −$429 866.67, with the negative sign demonstrating that acceptance was the dominant strategy. By utilizing QALYs and ICER scores we have shown that the acceptance of MAPPP app recommendations is the dominant strategy for the periprocedural management of patients on long-term anticoagulation.